PENGARUH WORKING CAPITAL TURNOVER, RECEIVABLE TURNOVER DAN FIRM SIZE TERHADAP PROFITABILITAS DIMODERASI LIKUIDITAS PADA PT. “LK” SEMARANG PERIODE 2013-2016 - Patricia Dhiana Paramita (Universitas Pandanaran, 2018)
In principle, the profitability of a company is affected by working capital turnover, receivable turnover and firm size. The analysis of working capital turnover, receivable turnover and firm size for each company is very important to do to determine the current financial condition of the company and the financial situation in the future. This study aims to determine the effect of working capital turnover, receivable turnover and firm size partially to profitability moderated by liquidity.Sources of data used are secondary data, which is related to the object of research, namely PT.